Pengaruh Manajemen Laba dan Strategi Bisnis terhadap Financial Distress pada Perusahaan Sub-Sektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - M. Ziqri Januarsa; Widya Rizki Eka Putri (AKUNTANSI 45, 2026)
This study analyzes the influence of earnings management and business strategy on financial distress in textile and garment companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research is motivated by increasing industrial challenges, including global competition, regulatory adjustments, and declining consumer purchasing power that affect companies’ financial conditions. This study employs a quantitative approach using secondary data obtained from annual financial reports. Logistic regression and multivariate discriminant analysis are applied to examine the relationship between variables and classify firms experiencing financial distress. The findings reveal that earnings management does not have a significant effect on financial distress, indicating that accounting manipulation practices are not the primary determinant of financial instability. In contrast, business strategy has a significant negative effect on financial distress, suggesting that effective operational and strategic management can reduce financial risk. Furthermore, the classification model demonstrates high predictive accuracy in identifying financially distressed firms. These results emphasize the importance of business strategy in maintaining financial stability.